Daily variation of macronutrient concentrations in mature human milk over 3 weeks - Gabriela E. Leghi (Nature Portfolio, 2021)
Abstract Human milk (HM) composition is known to be highly variable, both between individuals and across the duration of lactation. It is less clear, however, to what extent fat, lactose and protein concentrations in HM change daily over shorter time periods in mature HM, and no studies have evaluated this to date. The aim of this study was to systematically assess and compare HM macronutrient concentrations in samples collected at different times of day, from left and right breasts and daily across a 3-week period in the same woman. Fifteen lactating women (1.6–4.9 months postpartum) collected daily pre-feed HM samples from both breasts each morning for 21 consecutive days and completed intensive sampling once a week (morning, afternoon and evening samples) during this period. Concentrations of fat, protein and lactose in HM did not differ according to time of day, day of week or breast used for collection. The results of this study suggest that pre-feed samples collected at any point across a 3-week period and from either the left or right breast provide comparable measures of fat, protein and lactose concentrations in mature HM, in pragmatic studies where women are collecting their own HM samples. Clinical trial registration: Australian New Zealand Clinical Trials Registry (ACTRN12619000606189).